2024
DOI: 10.2196/54781
|View full text |Cite
|
Sign up to set email alerts
|

The Artificial Third: A Broad View of the Effects of Introducing Generative Artificial Intelligence on Psychotherapy

Yuval Haber,
Inbar Levkovich,
Dorit Hadar-Shoval
et al.

Abstract: This paper explores a significant shift in the field of mental health in general and psychotherapy in particular following generative artificial intelligence’s new capabilities in processing and generating humanlike language. Following Freud, this lingo-technological development is conceptualized as the “fourth narcissistic blow” that science inflicts on humanity. We argue that this narcissistic blow has a potentially dramatic influence on perceptions of human society, interrelationships, and the self. We shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…Since then, numerous studies have demonstrated the significant potential of this technology in various domains, including education, medicine, law, art, programming, and psychology. [11][12][13][14] LLMs are a cornerstone technology within the broader GenAI field, designed to understand, generate, and manipulate human-like texts based on vast amounts of training data. While GenAI encompasses various AI systems capable of creating new content (including images, audio, and code), LLMs specifically focus on language tasks, serving as the foundation for advanced natural language processing applications and driving significant improvements in AI's ability to interact with humans in more natural and contextually appropriate ways.…”
Section: Ai-based Technology In Mental Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, numerous studies have demonstrated the significant potential of this technology in various domains, including education, medicine, law, art, programming, and psychology. [11][12][13][14] LLMs are a cornerstone technology within the broader GenAI field, designed to understand, generate, and manipulate human-like texts based on vast amounts of training data. While GenAI encompasses various AI systems capable of creating new content (including images, audio, and code), LLMs specifically focus on language tasks, serving as the foundation for advanced natural language processing applications and driving significant improvements in AI's ability to interact with humans in more natural and contextually appropriate ways.…”
Section: Ai-based Technology In Mental Healthmentioning
confidence: 99%
“…These include data privacy, algorithmic opacity, threats to patient autonomy, risks of anthropomorphism, technology access disparities, corporate concentration, deep fakes, fake news, reduced reliance on professionals, and amplification of biases. 12,21,28,29 At a more philosophical level, questions arise regarding GenAI-human relationships, the prospect of generating intimacy, and how this may affect human-to-human relationships. 12,18,30 One promising domain in which GenAI has the potential to make a significant contribution to mental health is a global endeavor to prevent suicide.…”
Section: Ai-based Technology In Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the field of mental health indicate that AI models can optimize assistance and diagnostic processes, shorten the time required for administrative tasks, improve patient availability, and reduce stigma [5][6][7][8]. Despite these advantages, issues concerning ethics, privacy, and cultural bias still present difficulties [9][10][11]. Moreover, the results of these studies are inconsistent, often because of differing methodologies [12].…”
Section: Introductionmentioning
confidence: 99%